Pelatihan Strategi Komunikasi Efektif Untuk Implementasi Parenting Pada Wali Santri Pesantren Motivator Al Qur’an Tazakka Bogor - Arina Muntazah; Rindana Intan Emeilia; Rosiana Andhikasari; Abdul Aziz (LPPM Universitas Dharma Andalas, 2022)
In this era of increasingly modern development, many parents are worried about their children's associations which can easily deviate from social norms, so that not a few of today's Muslim parents entrust education and child care in Islamic boarding schools, in addition to aiming to mature religious knowledge, but also boarding schools are expected to cultivate the morals of their students so that they have noble character. However, it turns out that there are still many people who do not know that the responsibility for fostering children is not only on the part of the pesantren, parents also have a very important role in communicating with children to implement parenting in order to print their children to become good, moral individuals, and have a noble character as expected. In response to this, this Community Service activity is expected to make participants aware that it is very important to have skills in the field of parenting communication. The Community Service Partner (PM) is the Guardian of the Al-Qur'an Motivator Islamic Boarding School Tazakka Bogor, which is located at Jl. Raya Jampang Gang Masjid No.56 RT.02/RW.06, Jampang, Kemang, Bogor Regency, West Java 16310I. The solution that is expected to be a solution to the problems that are problems for the guardians of the Al Qur'an Motivator Islamic Boarding School Tazakka Bogor, namely: This Community Service activity is carried out directly face to face which is located in the pesantren hall while still paying attention to strict health protocols. The result of this training is an increase in the knowledge and skills of the guardians of students to implement parenting communication effectively.